2023
DOI: 10.1183/23120541.00653-2022
|View full text |Cite
|
Sign up to set email alerts
|

ERS International Congress 2022: highlights from the Paediatrics Assembly

Abstract: This review has been prepared by the Early Career Members and Chairs of the European Respiratory Society (ERS) Assembly 7: Paediatrics. We here summarise the highlights of the advances in paediatric respiratory research presented at the ERS International Congress 2022. The eight scientific Groups of this Assembly cover a wide range of research areas, including respiratory physiology and sleep, asthma and allergy, cystic fibrosis (CF), respiratory infection and immunology, neonatology and intensive care, respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…The ERS International Congress 2023 showed that advances in paediatric respiratory medicine are rapidly advancing. In line with previous years [ 82 , 83 ], we present a selection of the outstanding sessions on behalf of Assembly 7 (Paediatrics) in order to inform the reader of the latest developments and encourage participation in future ERS activities [ 84 ]. Overall, it has become evident that respiratory health in early life impacts respiratory health in childhood and adulthood, which underlines the need for collaboration among healthcare providers and researchers from different disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…The ERS International Congress 2023 showed that advances in paediatric respiratory medicine are rapidly advancing. In line with previous years [ 82 , 83 ], we present a selection of the outstanding sessions on behalf of Assembly 7 (Paediatrics) in order to inform the reader of the latest developments and encourage participation in future ERS activities [ 84 ]. Overall, it has become evident that respiratory health in early life impacts respiratory health in childhood and adulthood, which underlines the need for collaboration among healthcare providers and researchers from different disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Although the virtual platform allows presentations to be replayed, it can be challenging to keep up to date with all the scientific and clinical advances. That's why, every year, the Early-Career Members Committee coordinates reports summarising the most significant presentations from each Assembly [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. This article, therefore, aims to share some of the highlights from the Respiratory clinical care and physiology assembly.…”
Section: Introductionmentioning
confidence: 99%